Antimicrobial properties of Citrus maxima flavedo extracts against food pathogens and spoilage microorganisms - Mastuki, Mohd Fahmi; Yusoff, Noryuslina; Zainal Abidin, Nur Suraya (Science, Engineering and Health Studies, 2024)
This study assesses the antimicrobial potential of ethyl acetate and dichloromethane extracts obtained from pomelo, Citrus maxima (C. maxima), flavedo against various food pathogens and spoilage microorganisms. The antimicrobial activities of these extracts were evaluated using the agar disc diffusion method against gram-positive bacteria (Bacillus cereus), Staphylococcus aureus and gram-negative bacteria (Escherichia coli). The results indicated that both extracts demonstrated antibacterial properties against the tested microorganisms. The ethyl acetate extract exhibited significantly higher antibacterial activity against the majority of bacterial strains compared to the dichloromethane extract, particularly against S. aureus and B. cereus. However, dichloromethane extract showed a better effect on E. coli, with the inhibition zone ranging from 8.7 to 11.3 mm. S. aureus displayed the highest sensitivity to ethyl acetate and dichloromethane extracts of pomelo flavedo with inhibition zones ranging from 1.3 to 1.5 mm, respectively. In conclusion, the findings suggest that pomelo extracts have significant potential as natural antimicrobials and can be safely utilized as food preservatives. This highlights the value of pomelo as a potential source of antimicrobial compounds for food safety and preservation purposes.